Field features and petrography used as indicators for the classification of Shigar valley pegmatites, Gilgit-Baltistan region of Pakistan - Agheem, M. Hassan; Shah, Mohammad Tahir; Khan, Tahseenullah; Laghari, Amanullah; Dars, Humaira (Journal of Himalayan Earth Sciences, 2011)
On the basis of field features and petrography, Shigar valley pegmatites are classified broadly into Group-I and Group-II pegmatites. The Group-I pegmatites are further divided into muscovite-schorlberyl-garnet pegmatites and muscovite-schorl pegmatites. The muscovite-schorl-beryl-garnet pegmatites are more productive for gemstones. The Group-II pegmatites are classified as biotite ± garnet ± muscovite pegmatites and muscovite-biotite ± garnet pegmatites. The complete absence of biotite and the higher percentage of muscovite in the gemstone bearing class of pegmatites can be used as indicators for gemstone exploration.